Efeitos da ovariectomia associada ao trauma dentoalveolar sobre a movimentação dentária induzida de molares de ratos - Pasa , Adriana Paula Batista da Costa (2019)
The success of tooth movement in traumatized teeth depends on the severity of the injury, with root resorption being an undesirable and possible consequence to occur before, during and after orthodontic treatment. In addition, the patient's hormonal status has a major impact on the orthodontist's behavior, as it can directly influence treatment efficiency. Thus, the objective of this study was to evaluate the influence of estrogen deficiency on the histological structure of periodontal tissues and root resorption during the induced tooth movement of molars of rats submitted to extrusive luxation. For this, 48 Wistar rats were used, separated into eight experimental groups, with 6 animals each, as follows: Group 1: control; Group 2: animals submitted to dentoalveolar trauma (DT); Group 3: animals submitted to ovariectomy (OVX); Group 4: animals submitted to DT+OVX; Group 5: animals submitted to induced tooth movement (ITM); Group 6: animals submitted to ITM+DT; Group 7: animals submitted to ITM+OVX and Group 8: animals that underwent ITM+DT+OVX. The tooth movement rate was significantly higher in the animals of the ITM+DT+OVX group when compared to the other groups. The ITM+DT and ITM+OVX groups presented higher tooth movement when compared to the OTM group. Periodontal, radicular and bone alterations were found mainly in the groups with tooth movement and trauma, and in the association of movement, trauma and ovariectomy. The DT and DT+OVX groups had the highest areas of root resorption when compared to the CTL and OVX groups. All groups with a tooth movement device presented areas of root resorption greater than the animals of the groups without tooth movement device. There were no significant differences in areas of root resorption in the comparison between the ITM+DT and ITM+OVX groups, however, both presented greater areas of root resorption when compared to the ITM group and smaller compared to the ITM+DT+OVX group. The ITM+DT+OVX group had the highest amounts of root resorption areas when compared to all experimental groups. We conclude that induced tooth movement associated with dentoalveolar trauma and estrogen deficiency induce a higher rate of tooth movement and a higher occurrence of root resorption.